Aerosol optical properties as observed from an ultralight aircraft over the Strait of Gibraltar - P. Chazette (Atmospheric Measurement Techniques, 2020)
An unprecedented scientific flight was conducted over the Strait of Gibraltar to study the optical properties of the atmospheric aerosols from the sea surface to the lower free troposphere within the framework of the southern Spain experiment for spaceborne mission validation (SUSIE). A Rayleigh–Mie lidar was installed on an ultralight aircraft (ULA) for vertical (nadir) and horizontal line-of-sight measurements. This experiment took place on 13 August 2011 in parallel with continuous observations with a N2-Raman lidar from the coastal site of San Pedro Alcantara (∼ 50 km north-east of Gibraltar). Significant differences were observed between the optical properties of the aerosol layers sampled over the Strait of Gibraltar and San Pedro Alcantara. These differences are related to the surface–atmosphere interface in the planetary boundary layer and the origins and transport processes in the lower free troposphere. A significant contribution of terrigenous aerosols originating from the Iberian Peninsula is highlighted over the two areas. These polluted dusts are identified with lidar ratios (LRs) ∼45±8<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="8422c334c77fa4944838b288fe381775"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-13-4461-2020-ie00001.svg" width="42pt" height="10pt" src="amt-13-4461-2020-ie00001.png"/></svg:svg> sr higher than those of Saharan aerosols sampled during the same period (<34 sr) at 355 nm. Furthermore, the particle depolarization ratio is derived with values of ∼ 10 %–15 % for the polluted dust and >20 % for the Saharan dusts. The difference in LRs is the opposite of what is usually assumed for these two types of aerosols and highlights the need to update the classification of aerosols in terms of LR to be used in the inversion of vertical profiles from future spaceborne missions embedding a lidar operating at 355 nm.